Quantum dot devices and electronic devices
By introducing specific electrode layer structures into quantum dot devices, optimizing the transmission properties of electrons and holes, the problem of insufficient performance of existing quantum dot devices is solved, and more efficient luminescence and longer life are achieved.
Patent Information
- Application Number
- CN201910835922.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-01-15
- Filing Date
- 2019-09-05
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2039-09-05
AI Technical Summary
Existing quantum dot devices have shortcomings in performance and need improvements to improve efficiency and lifetime.
By introducing a hole transport layer, an inorganic electron transport layer and an inorganic electron control layer into the quantum dot device, the transmission properties of electrons and holes are optimized to improve the luminescence efficiency of the quantum dot layer and the stability of the device.
Improvements in quantum dot device performance are achieved, including improving luminescence efficiency and extending device life, and reducing unnecessary electron migration by optimizing the transmission properties of electrons and holes.
Smart Images

Figure CN111435710B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the priority of Korean Patent Application No. 10-2019-0005324 filed in the Korean Intellectual Property Office on January 15, 2019, and all rights and interests arising therefrom, the entire contents of which are incorporated herein by reference. Technical Field
[0003] Quantum dot devices and electronic devices are disclosed. Background Art
[0004] Unlike bulk materials, the physical properties of nanoparticles as intrinsic properties (e.g., energy band gap, melting point, etc.) can be controlled by changing the particle size of the nanoparticles. For example, when semiconductor nanocrystal particles, also called quantum dots, are supplied with light energy or electrical energy, the quantum dots can emit light of a wavelength corresponding to the size of the quantum dots. Therefore, quantum dots can be used as light-emitting elements that emit light of a specific wavelength. Summary of the invention
[0005] Quantum dot devices may use quantum dots as light emitting elements. Methods of improving the performance of quantum dot devices are needed.
[0006] One embodiment may provide a quantum dot device capable of achieving improved performance.
[0007] One embodiment provides an electronic device including the quantum dot device.
[0008] According to one embodiment, a quantum dot device includes: an anode and a cathode facing each other; a quantum dot layer between the anode and the cathode; a hole transport layer between the anode and the quantum dot layer, the hole transport layer being configured to improve the hole transport properties from the anode to the quantum dot layer; an inorganic electron transport layer between the cathode and the quantum dot layer, the inorganic electron transport layer being configured to improve the electron transport properties from the cathode to the quantum dot layer; and an inorganic electron control layer between the cathode and the quantum dot layer, the inorganic electron control layer being configured to reduce the electron transport properties from the cathode to the quantum dot layer.
[0009] The inorganic electron control layer may be disposed between the cathode and the inorganic electron transport layer, between the quantum dot layer and the inorganic electron transport layer, or a combination thereof.
[0010] The inorganic electron transport layer may include a first inorganic material, and the inorganic electron control layer may include a second inorganic material different from the first inorganic material.
[0011] The first inorganic material may include an oxide including zinc.
[0012] The zinc oxide may be composed of Zn 1-x M x O represents, wherein M is Mg, Co, Ni, Zr, Mn, Sn, Y, Al, or a combination thereof, and 0≤x<0.5.
[0013] The second inorganic material may include an oxide, a nitride, a sulfide, a phosphide, or a halide including gallium, nickel, copper, tungsten, manganese, chromium, tantalum, bismuth, indium, aluminum, lead, zirconium, or a combination thereof.
[0014] The second inorganic material may include γ-Ga 2 O 3 .
[0015] The first inorganic material may include Zn 1-x M x O represents an oxide containing zinc, wherein M is Mg, Co, Ni, Zr, Mn, Sn, Y, Al, or a combination thereof, and 0≤x<0.5, and the second inorganic material may include gallium oxide (gallium oxide).
[0016] The first inorganic material and the second inorganic material may each include nanoparticles having an average particle diameter of less than or equal to about 10 nanometers (nm).
[0017] A lowest unoccupied molecular orbital (LUMO) energy level of the inorganic electron control layer may be lower than a LUMO energy level of the quantum dot layer and a LUMO energy level of the inorganic electron transport layer, respectively.
[0018] The energy band gap of the inorganic electron control layer may be greater than the energy band gap of the quantum dot layer and the energy band gap of the inorganic electron transport layer.
[0019] The thickness of the inorganic electron control layer may be smaller than the thickness of the inorganic electron transport layer.
[0020] The inorganic electronic control layer may have a thickness of about 1 nm to about 10 nm.
[0021] The quantum dot layer may include non-cadmium-based (cadmium-free) quantum dots.
[0022] The non-cadmium-based quantum dots may include zinc (Zn) and tellurium (Te), selenium (Se), or a combination thereof, or indium (In) and zinc (Zn), phosphorus (P), or a combination thereof.
[0023] The quantum dot may include: a core comprising: zinc (Zn) and tellurium (Te), selenium (Se), or a combination thereof, or indium (In) and zinc (Zn), phosphorus (P), or a combination thereof; and a shell on at least a portion of the core, the shell comprising a composition different from that of the core.
[0024] The shell may include ZnSeS, ZnS, or a combination thereof.
[0025] According to one embodiment, a method for manufacturing a quantum dot device includes: forming an anode, forming a hole transport layer on the anode, forming a quantum dot layer on the hole transport layer, forming an inorganic electron transport layer on the quantum dot layer, forming an inorganic electron control layer on the quantum dot layer, and forming a cathode on the inorganic electron transport layer and the inorganic electron control layer, wherein the formation of the inorganic electron control layer is performed before the formation of the inorganic electron transport layer, after the formation of the inorganic electron transport layer, or a combination thereof, and the formation of the quantum dot layer, the formation of the inorganic electron transport layer, and the formation of the inorganic electron control layer are each performed using a solution process.
[0026] The formation of the inorganic electron transport layer may include: preparing a Zn precursor and an optional M precursor by a sol-gel reaction using a solution including a Zn precursor and an optional M precursor; 1-x M x O, wherein M is Mg, Co, Ni, Zr, Mn, Sn, Y, Al, or a combination thereof, and coating the dispersion for an inorganic electron transport layer; and forming the inorganic electron control layer may include: heat treating a solution including a Ga precursor to prepare a solution including γ-Ga 2 O 3 A dispersion of inorganic nanoparticles for an inorganic electronic control layer, and coating of the dispersion for an inorganic electronic control layer.
[0027] According to an embodiment, an electronic device includes the quantum dot device.
[0028] The performance of the quantum dot devices (eg, efficiency and lifetime) may be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1-3 is a schematic cross-sectional view showing a quantum dot device according to an embodiment,
[0030] Figure 4 is a graph of counts versus 2θ (coupled two theta / theta), which shows an X-ray diffraction (XRD) pattern of a thin film obtained from the dispersion for an electron control layer obtained in Preparation Example 2,
[0031] Figure 5 and 6are graphs of intensity (arbitrary unit (au)) versus binding energy (electron volt (eV)), which respectively show the results of X-ray photoelectron spectroscopy (XPS) analysis of a thin film obtained from the dispersion for an electron control layer obtained in Preparation Example 2, and
[0032] Figure 7 is an atomic force microscope (AFM) photograph showing the morphology of a thin film obtained from the dispersion for an electron control layer obtained in Preparation Example 2. DETAILED DESCRIPTION
[0033] Hereinafter, example embodiments of the present disclosure will be described in detail so that those skilled in the art will understand it. However, the present disclosure may be embodied in many different forms and is not to be construed as limited to the example embodiments set forth herein.
[0034] In the accompanying drawings, the thickness of layers, films, panels, regions, etc., is exaggerated for clarity. Throughout the specification, the same reference numerals represent the same elements. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or there can be intermediate elements. On the contrary, when an element is referred to as being "directly on" another element, there are no intermediate elements.
[0035] It will be understood that although the terms "first", "second", "third", etc. may be used herein to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the teachings herein, the first "element", "component", "region", "layer" or "part" discussed below may be referred to as a second element, component, region, layer or part.
[0036] The terms used herein are only for describing specific embodiments and are not intended to be restrictive. As used herein, the singular forms "one (kind)" and "the (said)" are intended to include plural forms, including "at least one (kind)", unless the content clearly indicates otherwise. "At least one (kind)" will not be interpreted as being limited to "one (kind)". "Or" means "and / or". As used herein, the term "and / or" includes any and all combinations of one or more of the relevant enumerated items. It will be further understood that when used in this specification, the term "comprising" or "including" indicates the presence of stated features, regions, wholes, steps, operations, elements, and / or components, but does not exclude the presence or addition of one or more other features, regions, wholes, steps, operations, elements, components, and / or their collections.
[0037] As used herein, "about" includes the stated value and means within an acceptable range of deviation for a particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" may mean that the deviation from the stated value is within one or more standard deviations, or within a range of ±30%, 20%, 10%, or 5%.
[0038] Unless otherwise defined, all terms (including technical and scientific terms) used in this article have the same meaning as commonly understood by ordinary technicians in the field to which the present disclosure belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as their meanings consistent with their meanings in the context of the present disclosure and the relevant art, and will not be interpreted in an idealized or overly formal sense unless clearly defined in this article.
[0039] Exemplary embodiments are described herein with reference to cross-sectional views as schematic diagrams of idealized embodiments. Thus, deviations from the illustrated shapes as a result of, for example, manufacturing techniques and / or tolerances are expected. Therefore, the embodiments described herein should not be construed as limited to the specific shapes of the regions as illustrated herein, but will include deviations in shape caused by, for example, manufacturing. For example, a region illustrated or described as flat may typically have rough and / or nonlinear features. Moreover, the illustrated sharp corners may be rounded. Therefore, the regions shown in the figures are schematic in nature, and their shapes are not intended to illustrate the precise shapes of the regions and are not intended to limit the scope of the claims.
[0040] Hereinafter, the work function, the highest occupied molecular orbital (HOMO) energy level, and the lowest unoccupied molecular orbital (LUMO) energy level are expressed as absolute values from the vacuum energy level. In addition, when the work function, the HOMO energy level, and the LUMO energy level are referred to as "deep", "high", or "large", the work function, the HOMO energy level, and the LUMO energy level have an absolute value of a vacuum energy level with a large distance of "0 electron volt (eV)", and when the work function, the HOMO energy level, and the LUMO energy level are referred to as "shallow", "low", or "small", the work function, the HOMO energy level, and the LUMO energy level have an absolute value of a vacuum energy level with a small distance of "0 eV".
[0041] Hereinafter, a quantum dot device according to an embodiment is described with reference to the accompanying drawings.
[0042] Figure 1-3 is a schematic cross-sectional view of a quantum dot device according to an embodiment.
[0043] Reference Figure 1-3According to the embodiment, the quantum dot device 10 includes: an anode 11 and a cathode 16; a quantum dot layer 13 arranged between the anode 11 and the cathode 16; a hole transport layer 12 arranged between the anode 11 and the quantum dot layer 13; and an electron transport layer 14 and an electron control layer 15 arranged between the cathode 16 and the quantum dot layer 13.
[0044] A substrate may be provided at the anode 11 or cathode 16 side. The substrate may be made of, for example, an inorganic material such as glass; an organic material such as polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyethersulfone, or a combination thereof; or a silicon wafer. The substrate may be omitted.
[0045] The anode 11 may be made of a conductor having a high work function, and may be made of, for example, a metal, a conductive metal oxide, or a combination thereof. The anode 11 may be made of, for example, a metal or an alloy thereof such as nickel, platinum, vanadium, chromium, copper, zinc, gold, or a combination thereof; a conductive metal oxide such as zinc oxide, indium oxide, tin oxide, indium tin oxide (ITO), indium zinc oxide (IZO), or fluorine-doped tin oxide; or a combination of a metal and an oxide such as ZnO and Al or SnO 2 and Sb, but not limited thereto.
[0046] The cathode 16 may be made of, for example, a conductor having a work function smaller than that of the anode 11, and may be made of, for example, a metal, a conductive metal oxide, a conductive polymer, or a combination thereof. The cathode 16 may be, for example, a metal or an alloy thereof such as aluminum, magnesium, calcium, sodium, potassium, titanium, indium, yttrium, lithium, gadolinium, silver, tin, lead, cesium, barium, or a combination thereof; or a multilayer structure material such as LiF / Al, LiO 2 / Al, Liq / Al, LiF / Ca, and BaF 2 / Ca, but not limited thereto.
[0047] The work function of the anode 11 may be higher than the work function of the cathode 16. For example, the work function of the anode 11 may be, for example, about 4.5 eV to about 5.0 eV, and the work function of the cathode 16 may be, for example, greater than or equal to about 4.0 eV and less than about 4.5 eV. Within the range, the work function of the anode 11 may be, for example, about 4.6 eV to about 4.9 eV, and the work function of the cathode 16 may be, for example, about 4.0 eV to about 4.3 eV.
[0048] The anode 11, the cathode 16, or a combination thereof may be a light-transmitting electrode, and the light-transmitting electrode may be made, for example, of a conductive oxide such as zinc oxide, indium oxide, tin oxide, indium tin oxide (ITO), indium zinc oxide (IZO), or fluorine-doped tin oxide, or a single or multiple metal thin layer. When one of the anode 11 and the cathode 16 is a non-light-transmitting electrode, the non-light-transmitting electrode may be made, for example, of an opaque conductor such as aluminum (Al), silver (Ag), or gold (Au).
[0049] The quantum dot layer 13 includes quantum dots. The quantum dots may be semiconductor nanocrystals and may have a variety of shapes, such as spherical semiconductor nanocrystals, quantum rods, and quantum sheets. Here, the quantum rod may refer to a quantum dot having an aspect ratio greater than about 1:1, such as greater than or equal to about 2:1, greater than or equal to about 3:1, or greater than or equal to about 5:1. For example, the quantum rod may have an aspect ratio less than or equal to about 50:1, less than or equal to about 30:1, or less than or equal to about 20:1.
[0050] The quantum dots may have a particle size (for non-spherical shapes, the length of the largest portion) of, for example, about 1 nm to about 100 nm, about 1 nm to about 80 nm, about 1 nm to about 50 nm, or about 1 nm to about 20 nm.
[0051] The energy band gap of the quantum dots can be controlled according to the size and composition of the quantum dots, and thus the photoluminescence wavelength can be controlled. For example, as the size of the quantum dots increases, the quantum dots may have a relatively narrow energy band gap and emit light in a relatively long wavelength region, while as the size of the quantum dots decreases, the quantum dots may have a relatively wide energy band gap and emit light in a relatively short wavelength region.
[0052] For example, depending on the size of the quantum dots, the composition of the quantum dots, or a combination thereof, the quantum dots may emit light, for example, in a predetermined wavelength region in the visible light region. For example, the quantum dots may emit blue light, red light, or green light, and the blue light may have, for example, a peak emission wavelength in a wavelength region of about 430 nm to about 470 nm, the red light may have, for example, a peak emission wavelength in a wavelength region of about 600 nm to about 650 nm, and the green light may have, for example, a peak emission wavelength in a wavelength region of about 520 nm to about 550 nm. For example, the quantum dots may emit blue light having a peak emission wavelength in a wavelength region of about 430 nm to about 470 nm.
[0053] For example, the average size of quantum dots emitting blue light may be, for example, less than or equal to about 4.5 nm, less than or equal to about 4.3 nm, less than or equal to about 4.2 nm, less than or equal to about 4.1 nm, or less than or equal to 4.0 nm. Within the range, the average size of quantum dots emitting blue light may be, for example, from about 2.0 nm to about 4.5 nm, from about 2.0 nm to about 4.3 nm, from about 2.0 nm to about 4.2 nm, from about 2.0 nm to about 4.1 nm, or from about 2.0 nm to about 4.0 nm. As used herein, in the case of a single quantum dot, the phrase "average size" refers to the size of the quantum dot.
[0054] The quantum dots may have a quantum yield of, for example, greater than or equal to about 10%, greater than or equal to about 30%, greater than or equal to about 50%, greater than or equal to about 60%, greater than or equal to about 70%, or greater than or equal to about 90%.
[0055] The quantum dots may have a relatively narrow full width at half maximum (FWHM). Herein, FWHM is a wavelength width corresponding to half of a peak absorption point, and as the FWHM is narrower, light in a narrower wavelength region may be emitted and high color purity may be obtained. The quantum dots may have a FWHM of, for example, about 50 nm or less, about 49 nm or less, about 48 nm or less, about 47 nm or less, about 46 nm or less, about 45 nm or less, about 44 nm or less, about 43 nm or less, about 42 nm or less, about 41 nm or less, about 40 nm or less, about 39 nm or less, about 38 nm or less, about 37 nm or less, about 36 nm or less, about 35 nm or less, about 34 nm or less, about 33 nm or less, about 32 nm or less, about 31 nm or less, about 30 nm or less, about 29 nm or less, or about 28 nm or less.
[0056] For example, the quantum dots may be, for example, II-VI semiconductor compounds, III-V semiconductor compounds, IV-VI semiconductor compounds, IV semiconductor elements or compounds, I-III-VI semiconductor compounds, I-II-IV-VI semiconductor compounds, II-III-V semiconductor compounds, or combinations thereof. The II-VI semiconductor compounds may be, for example, binary compounds of CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, MgSe, MgS, or combinations thereof; CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdH Ternary compounds of ZnSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, MgZnSe, MgZnS, or combinations thereof; quaternary compounds of ZnSeSTe, HgZnTeS, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe, or combinations thereof; or combinations thereof, but are not limited thereto. The III-V semiconductor compound may be, for example, a binary compound of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, or a combination thereof; a ternary compound of GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, or a combination thereof; a quaternary compound of GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb, or a combination thereof; or a combination thereof, but is not limited thereto. The IV-VI semiconductor compound may be, for example: a binary compound of SnS, SnSe, SnTe, PbS, PbSe, PbTe, or a combination thereof; a ternary compound of SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, or a combination thereof; a quaternary compound of SnPbSSe, SnPbSeTe, SnPbSTe, or a combination thereof; or a combination thereof, but is not limited thereto.The IV group semiconductor element or compound may be, for example, a simple semiconductor of Si, Ge, or a combination thereof; a binary semiconductor of SiC, SiGe, or a combination thereof; or a combination thereof, but is not limited thereto. The I-III-VI group semiconductor compound may be, for example, selected from CuInSe. 2 、CuInS 2 , CuInGaSe, CuInGaS, or a combination thereof, but not limited thereto. The I-II-IV-VI group semiconductor compound may be, for example, CuZnSnSe, CuZnSnS, or a combination thereof, but not limited thereto. The II-III-V group semiconductor compound may include, for example, InZnP, but not limited thereto.
[0057] The quantum dots may include the binary semiconductor compound, the ternary semiconductor compound, or the quaternary semiconductor compound distributed in a substantially uniform concentration or in a locally different concentration.
[0058] For example, the quantum dots may include non-cadmium-based quantum dots. Cadmium (Cd) may cause serious environmental / health problems and is a restricted element of the Restriction of Hazardous Substances (RoHS) directive in many countries, so the non-cadmium-based quantum dots may be effectively used.
[0059] For example, the quantum dot may be a semiconductor compound including zinc (Zn) and tellurium (Te), selenium (Se), or a combination thereof. For example, the quantum dot may be a Zn-Te semiconductor compound, a Zn-Se semiconductor compound, a Zn-Te-Se semiconductor compound, or a combination thereof. For example, in the Zn-Te-Se semiconductor compound, the amount of tellurium (Te) may be less than the amount of selenium (Se). The semiconductor compound may have a peak emission wavelength in a wavelength region less than or equal to about 470 nm, for example, in a wavelength region of about 430 nm to about 470 nm, and may emit blue light.
[0060] For example, the quantum dots may be semiconductor compounds including, for example, indium (In) and zinc (Zn), phosphorus (P), or a combination thereof. For example, the quantum dots may be In-Zn semiconductor compounds, In-P semiconductor compounds, In-Zn-P semiconductor compounds, or a combination thereof. For example, in the In-Zn semiconductor compound or the In-Zn-P semiconductor compound, the molar ratio of zinc (Zn) to indium (In) may be greater than or equal to about 25:1. The semiconductor compound may have a peak emission wavelength in a wavelength region less than or equal to about 470 nm, for example, in a wavelength region of about 430 nm to about 470 nm, and may emit blue light.
[0061] The quantum dot may have a core-shell structure in which one quantum dot surrounds another quantum dot. For example, the core and shell of the quantum dot may have an interface, and the element of the core, the element of the shell, or a combination thereof in the interface may have a concentration gradient, for example, the concentration of the element of the shell may decrease toward the core. For example, the material composition of the shell of the quantum dot may have a higher band gap than the material composition of the core of the quantum dot, and the quantum dot may exhibit a quantum confinement effect.
[0062] The quantum dot may have a quantum dot core and a multi-layer quantum dot shell surrounding the core. Here, the multi-layer shell has at least two shells, wherein each shell may include, for example, a single composition, an alloy, a concentration gradient, or a combination thereof.
[0063] For example, a shell of a multi-layer shell that is far from the core, such as relatively farther, may have a higher band gap than a shell that is close to, such as relatively closer to, the core, and the quantum dot may exhibit a quantum confinement effect.
[0064] For example, a quantum dot having a core-shell structure may, for example, include: a core comprising a first semiconductor compound, the first semiconductor compound comprising zinc (Zn) and tellurium (Te), selenium (Se), or a combination thereof; and a shell disposed on at least a portion of the core and comprising a second semiconductor compound having a composition different from the composition of the core.
[0065] For example, the first semiconductor compound may be a Zn-Te-Se based semiconductor compound including zinc (Zn), tellurium (Te) and selenium (Se), such as a Zn-Se based semiconductor compound including a small amount of tellurium (Te), such as a ZnTe-Se based semiconductor compound. x Se 1-x (wherein x is greater than approximately 0 and less than or equal to approximately 0.05).
[0066] For example, in the first semiconductor compound based on Zn-Te-Se, the molar amount of zinc (Zn) may be greater than the molar amount of selenium (Se), and the molar amount of selenium (Se) may be greater than the molar amount of tellurium (Te). For example, in the first semiconductor compound, the molar ratio of tellurium (Te) to selenium (Se) may be less than or equal to about 0.05:1, less than or equal to about 0.049:1, less than or equal to about 0.048:1, less than or equal to about 0.047:1, less than or equal to about 0.045:1, less than or equal to about 0.044:1, less than or equal to about 0.043:1, less than or equal to about 0.042:1, less than or equal to about 0.041:1, less than or equal to about 0.04:1, less than or equal to about 0.039:1, less than or equal to about 0.035:1, less than or equal to about 0.03:1, less than or equal to about 0.029:1 1, less than or equal to about 0.025:1, less than or equal to about 0.024:1, less than or equal to about 0.023:1, less than or equal to about 0.022:1, less than or equal to about 0.021:1, less than or equal to about 0.02:1, less than or equal to about 0.019:1, less than or equal to about 0.018:1, less than or equal to about 0.017:1, less than or equal to about 0.016:1, less than or equal to about 0.015:1, less than or equal to about 0.014:1, less than or equal to about 0.013:1, less than or equal to about 0.012:1, less than or equal to about 0.011:1, or less than or equal to about 0.01:1. For example, in the first semiconductor compound, the molar ratio of tellurium (Te) to zinc (Zn) may be less than or equal to about 0.02:1, less than or equal to about 0.019:1, less than or equal to about 0.018:1, less than or equal to about 0.017:1, less than or equal to about 0.016:1, less than or equal to about 0.015:1, less than or equal to about 0.014:1, less than or equal to about 0.013:1, less than or equal to about 0.012:1, less than or equal to about 0.011:1, or less than or equal to about 0.01:1.
[0067] The second semiconductor compound may include, for example, a II-VI semiconductor compound, a III-V semiconductor compound, an IV-VI semiconductor compound, a IV semiconductor element or compound, an I-III-VI semiconductor compound, an I-II-IV-VI semiconductor compound, a II-III-V semiconductor compound, or a combination thereof. Examples of the II-VI semiconductor compound, the III-V semiconductor compound, the IV-VI semiconductor compound, the IV semiconductor element or compound, the I-III-VI semiconductor compound, the I-II-IV-VI semiconductor compound, and the II-III-V semiconductor compound are the same as described above.
[0068] For example, the second semiconductor compound may include zinc (Zn) and selenium (Se), sulfur (S), or a combination thereof. For example, the shell may include ZnSeS, ZnS, or a combination thereof. For example, the shell may include at least one inner shell disposed close to, for example, relatively closer to, the core and an outermost shell disposed at the outermost layer of the shell of the quantum dot, and the inner shell may include ZnSeS and the outermost shell may include ZnS. For example, the shell may have a concentration gradient of one component, and, for example, the amount of sulfur (S) may increase as it moves away from the core.
[0069] For example, a quantum dot having a core-shell structure may include, for example: a core including a third semiconductor compound, the third semiconductor compound including indium (In) and phosphorus (P), and optionally zinc (Zn); and a shell disposed on at least a portion of the core and including a fourth semiconductor compound having a composition different from that of the core.
[0070] In the third semiconductor compound based on In-Zn-P, a molar ratio of zinc (Zn) to indium (In) may be greater than or equal to about 25: 1. For example, in the third semiconductor compound based on In-Zn-P, a molar ratio of zinc (Zn) to indium (In) may be greater than or equal to about 28: 1, greater than or equal to about 29: 1, or greater than or equal to about 30: 1. For example, in the third semiconductor compound based on In-Zn-P, a molar ratio of zinc (Zn) to indium (In) may be less than or equal to about 55: 1, for example, less than or equal to about 50: 1, less than or equal to about 45: 1, less than or equal to about 40: 1, less than or equal to about 35: 1, less than or equal to about 34: 1, less than or equal to about 33: 1, or less than or equal to about 32: 1.
[0071] The fourth semiconductor compound may include, for example, a II-VI semiconductor compound, a III-V semiconductor compound, a IV-VI semiconductor compound, a IV semiconductor element or compound, a I-III-VI semiconductor compound, a I-II-IV-VI semiconductor compound, a II-III-V semiconductor compound, or a combination thereof. Examples of the II-VI semiconductor compound, the III-V semiconductor compound, the IV-VI semiconductor compound, the IV semiconductor element or compound, the I-III-VI semiconductor compound, the I-II-IV-VI semiconductor compound, and the II-III-V semiconductor compound are the same as described above.
[0072] For example, the fourth semiconductor compound may include zinc (Zn) and sulfur (S), and optionally selenium (Se). For example, the shell may include ZnSeS, ZnS, or a combination thereof. For example, the shell may include at least one inner shell disposed close to, for example relatively closer to, the core and an outermost shell disposed at the outermost layer of the shell of the quantum dot, and the inner shell, the outermost shell, or a combination thereof may include a fourth semiconductor compound ZnS or ZnSeS.
[0073] The quantum dot layer 13 may have a thickness of, for example, about 5 nm to about 200 nm, for example, about 10 nm to about 150 nm, about 10 nm to about 100 nm, or about 10 nm to about 50 nm.
[0074] The quantum dot layer 13 may have a relatively high HOMO energy level and may be, for example, a HOMO energy level of about 5.4 eV or more, about 5.6 eV or more, about 5.7 eV or more, about 5.8 eV or more, about 5.9 eV or more, or about 6.0 eV or more. The HOMO energy level of the quantum dot layer 13 may be, for example, about 5.4 eV to about 7.0 eV, about 5.4 eV to about 6.8 eV, about 5.4 eV to about 6.7 eV, about 5.4 eV to about 6.5 eV, about 5.4 eV to about 6.3 eV, about 5.4 eV to about 6.2 eV, or about 5.4 eV to about 6.1 eV, within the range, for example, about 5.6 eV to about 7.0 eV, about 5.6 eV to about 6.8 eV, about 5.6 eV to about 6.7 eV, about 5.6 eV to about 6.5 eV, about 5.6 eV to about 6.3 eV, about 5.6 eV to about 6.2 eV, or about 5.6 eV to about 6.1 eV, for example, about 5.7 eV to about 7.0 eV, about 5.7 eV to about 6.8 eV, about 5.6 eV to about 6.7 eV .7eV to about 6.7eV, about 5.7eV to about 6.5eV, about 5.7eV to about 6.3eV, about 5.7eV to about 6.2eV, or about 5.7eV to about 6.1eV, for example, about 5.8eV to about 7.0eV, about 5.8eV to about 6.8eV, about 5.8eV to about 6.7eV, about 5.8eV to about 6.5eV, about 5.8eV to about 6.3eV, about 5.8eV to about 6.2eV, about 5.8eV to about 6.1eV, for example, about 6.0eV to about 7.0eV, about 6.0eV to about 6.8eV, about 6.0eV to about 6.7eV, about 6.0eV to about 6.5eV, about 6.0eV to about 6.3eV, or about 6.0eV to about 6.2eV.
[0075] The quantum dot layer 13 may have a relatively low LUMO energy level, and may have, for example, a LUMO energy level of about 3.6 eV or less, such as about 3.5 eV or less, about 3.4 eV or less, about 3.3 eV or less, about 3.2 eV or less, or about 3.0 eV or less. The LUMO energy level of the quantum dot layer 13 may be, for example, about 2.5 eV to about 3.6 eV, about 2.5 eV to about 3.5 eV, about 2.5 eV to about 3.4 eV, about 2.5 eV to about 3.3 eV, about 2.5 eV to about 3.2 eV, about 2.5 eV to about 3.1 eV, or about 2.5 eV to about 3.0 eV.
[0076] The quantum dot layer 13 may have an energy band gap of about 2.4 eV to about 2.9 eV. Within the range, the quantum dot layer 13 may have an energy band gap of, for example, about 2.4 eV to about 2.8 eV, for example, about 2.4 eV to about 2.78 eV.
[0077] The hole transport layer 12 is disposed between the anode 11 and the quantum dot layer 13. The hole transport layer 12 may have one layer or two or more layers, and may improve hole transport properties from the anode 11 to the quantum dot layer 13.
[0078] The hole transport layer 12 may have a relatively high HOMO energy level so that the HOMO energy level of the hole transport layer 12 may match the HOMO energy level of the quantum dot layer 13. Therefore, hole transport properties from the hole transport layer 12 to the quantum dot layer 13 may be improved.
[0079] The hole transport layer 12 may have the same HOMO energy level as the quantum dot layer 13, or may have a HOMO energy level that differs from the HOMO energy level of the quantum dot layer 13 by less than about 1.0 eV or less. For example, the difference between the HOMO energy levels of the hole transport layer 12 and the quantum dot layer 13 may be about 0 eV to about 1.0 eV, such as about 0.01 eV to about 0.8 eV, about 0.01 eV to about 0.7 eV, about 0.01 eV to about 0.5 eV, about 0.01 eV to about 0.4 eV, about 0.01 eV to about 0.3 eV, about 0.01 eV to about 0.2 eV, or about 0.01 eV to about 0.1 eV.
[0080] The hole transport layer 12 may have a HOMO energy level of, for example, greater than or equal to about 5.0 eV, greater than or equal to about 5.2 eV, greater than or equal to about 5.4 eV, greater than or equal to about 5.6 eV, or greater than or equal to about 5.8 eV.
[0081] For example, the hole transport layer 12 may have a voltage of about 5.0 eV to about 7.0 eV, such as about 5.2 eV to about 6.8 eV, about 5.4 eV to about 6.8 eV, about 5.4 eV to about 6.7 eV, about 5.4 eV to about 6.5 eV, about 5.4 eV to about 6.3 eV, about 5.4 eV to about 6.2 eV, about 5.4 eV to about 6.1 eV, about 5.6 eV to about 7.0 eV, about 5.6 eV to about 6.8 eV, about 5.6 .... The present invention relates to a HOMO level of about 5.7 eV, about 5.6 eV to about 6.5 eV, about 5.6 eV to about 6.3 eV, about 5.6 eV to about 6.2 eV, about 5.6 eV to about 6.1 eV, about 5.8 eV to about 7.0 eV, about 5.8 eV to about 6.8 eV, about 5.8 eV to about 6.7 eV, about 5.8 eV to about 6.5 eV, about 5.8 eV to about 6.3 eV, about 5.8 eV to about 6.2 eV, or about 5.8 eV to about 6.1 eV.
[0082] The hole transport layer 12 may include any material that satisfies the energy level without particular limitation, and may be, for example, poly[(9,9-dioctylfluorene-2,7-diyl)-co-(4,4′-(N-(4-butylphenyl))-diphenylamine)] (TFB), polyarylamine (polyarylamine), poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N′,N′-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4,4′-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), m-MTDATA (4,4′,4″-tris[phenyl(m-tolyl)amino]triphenylamine), 4,4′,4″-tris(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenyl]cyclohexane (TAPC), p-type metal oxides (e.g., NiO, WO 3 、MoO 3 etc.), carbon-based materials such as graphene oxide, or combinations thereof, but are not limited thereto.
[0083] If necessary, a hole injection layer may be provided between the anode 11 and the hole transport layer 12. The hole injection layer may facilitate hole injection from the anode 11. The hole injection layer may have a HOMO level of about 5.0 eV to about 6.0 eV, about 5.0 eV to about 5.5 eV, or about 5.0 eV to about 5.4 eV. The hole injection layer may include, for example, poly(3,4-ethylenedioxythiophene) (PEDOT) or poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), but is not limited thereto.
[0084] The electron transport layer 14 is disposed between the cathode 16 and the quantum dot layer 13. The electron transport layer 14 can improve the electron transport properties from the cathode 16 to the quantum dot layer 13. The electron transport layer 14 may be an inorganic electron transport layer made of an inorganic material or including an inorganic material as a main component. Here, the main component may be included in the electron transport layer 14 in an amount of greater than or equal to about 50% by volume, greater than or equal to about 60% by volume, greater than or equal to about 70% by volume, greater than or equal to about 80% by volume, greater than or equal to about 90% by volume, greater than or equal to about 95% by volume, greater than or equal to about 98% by volume, greater than or equal to about 99% by volume, or about 100% by volume.
[0085] The electron transport layer 14 may, for example, include a first inorganic material. The first inorganic material may include, for example, inorganic nanoparticles. The inorganic nanoparticles may have, for example, an average particle size in the range of less than or equal to about 10 nm, for example, about 1 nm to about 10 nm, for example, about 2 nm to about 10 nm, and for example, about 3 nm to about 8 nm. As used herein, in the case of a single inorganic nanoparticle, the phrase "average particle size" refers to the particle size of the inorganic nanoparticle.
[0086] For example, the first inorganic material may include an oxide including zinc. The oxide including zinc may be an oxide including zinc as a main component and optionally doped with another metal or semi-metal, such as Zn. 1-x M x O (wherein M is Mg, Co, Ni, Zr, Mn, Sn, Y, Al, or a combination thereof, 0≤x<0.5).
[0087] For example, M may be Mg, Co, Ni, or a combination thereof, and x may be in the range of about 0.01≤x≤0.4, about 0.02≤x≤0.4, about 0.03≤x≤0.3, or about 0.05≤x≤0.3.
[0088] For example, the first inorganic material may include ZnO nanoparticles, Zn 1-x Mg x O nanoparticles, or a combination thereof.
[0089] The LUMO energy level of the electron transport layer 14 may be higher than the LUMO energy level of the quantum dot layer 13, and may be, for example, in the range of about 3.0 eV to about 5.3 eV, about 3.2 eV to about 5.3 eV, about 3.3 eV to about 5.3 eV, about 3.5 eV to about 5.3 eV, or about 3.7 eV to about 5.3 eV.
[0090] The electron transport layer 14 may have a thickness of about 5 nm to about 50 nm.
[0091] In contrast to, for example, substantially different from, the electron transport layer 14, the electron control layer 15 can reduce the electron transport properties from the cathode 16 to the quantum dot layer 13. In a quantum dot device 10 in which the electron mobility is faster than the hole mobility, the electron control layer 15 can reduce the electron mobility from the cathode 16 to the quantum dot layer 13, thereby reducing the imbalance between the number of electrons and the number of holes reaching the quantum dot layer 13. Therefore, the balance between the number of electrons and the number of holes in the quantum dot layer 13 is improved while the extra electrons are reduced, and as a result, the efficiency and lifetime of the quantum dot device 10 can be improved.
[0092] For example, the electron control layer 15 may form an energy barrier along the LUMO energy level in which electrons move, for example, the LUMO energy level of the electron control layer 15 may be lower than the LUMO energy levels of the quantum dot layer 13 and the electron transport layer 14. For example, the electron control layer 15 may have a LUMO energy level ranging from about 2.0 eV to about 3.0 eV.
[0093] For example, the energy band gap (Eg) of the electron control layer 15 may be respectively greater than the energy band gaps of the quantum dot layer 13 and the electron transport layer 14. For example, the energy band gap of the electron control layer 15 may be in the range of about 2.9 eV to about 5.5 eV.
[0094] For example, the electron mobility of the electron control layer 15 may be less than the electron mobility of the electron transport layer 14 , for example, the electron mobility of the electron control layer 15 may be about 0.2 to 0.9 times, about 0.3 to about 0.8 times, or about 0.4 to about 0.7 times the electron mobility of the electron transport layer 14 .
[0095] The electron control layer 15 may be disposed at one surface or both surfaces of the electron transport layer 14 between the cathode 16 and the quantum dot layer 13. In other words, the electron control layer 15 may be disposed between the cathode 16 and the electron transport layer 14, between the quantum dot layer 13 and the electron transport layer 14, or a combination thereof.
[0096] For example, Figure 1 As shown in , the electron control layer 15 may be disposed between the cathode 16 and the electron transport layer 14 .
[0097] For example, Figure 2 As shown in FIG. 1 , the electron control layer 15 may be disposed between the quantum dot layer 13 and the electron transport layer 14 .
[0098] For example, Figure 3 As shown in , the electron control layer 15 may be disposed between the cathode 16 and the electron transport layer 14 and between the quantum dot layer 13 and the electron transport layer 14 .
[0099] The electronic control layer 15 may be an inorganic electronic control layer made of an inorganic material or including an inorganic material as a main component. Here, the main component may be included in the electronic control layer 15 in an amount of about 50% by volume or more, about 60% by volume or more, about 70% by volume or more, about 80% by volume or more, about 90% by volume or more, about 95% by volume or more, about 98% by volume or more, about 99% by volume or more, or about 100% by volume.
[0100] The electronic control layer 15 may include, for example, a second inorganic material different from the first inorganic material above. The second inorganic material may include, for example, inorganic nanoparticles. The inorganic nanoparticles may have, for example, an average particle size of less than or equal to about 10 nm, about 1 nm to about 10 nm, about 2 nm to about 10 nm, or about 3 nm to about 8 nm. As used herein, in the case of a single inorganic nanoparticle, the phrase "average particle size" refers to the particle size of the inorganic nanoparticle.
[0101] For example, the second inorganic material may be an oxide, nitride, sulfide, phosphide, halide, or a combination thereof including a metal, a semimetal, or a combination thereof. For example, the second inorganic material may be an oxide, nitride, sulfide, phosphide, halide, or a combination thereof including gallium (Ga), nickel (Ni), copper (Cu), tungsten (W), manganese (Mn), chromium (Cr), tantalum (Ta), bismuth (Bi), indium (In), aluminum (Al), lead (Pb), zirconium (Zr), or a combination thereof. For example, the second inorganic material may be an oxide, nitride, sulfide, phosphide, halide, or a combination thereof having a crystal structure, such as a perovskite oxide. For example, the second inorganic material may include: oxides, such as gallium oxide, zirconium oxide, manganese oxide, chromium oxide, potassium tantalum oxide, bismuth oxide, indium oxide, aluminum oxide, or a combination thereof; nitrides such as aluminum nitride; sulfides such as manganese sulfide; phosphides such as gallium phosphide; halides such as lead bromide, lead iodide, or a combination thereof; or a combination thereof. For example, the second inorganic material may include Ga 2 O 3 、ZrO 2 、MnO、Cr 2 O 3 , KTaO 3 、Bi 2 O 3 、In 2 O 3 、Al 2 O 3 、AlN、MnS、GaP、MAPbBr 3 (methylammonium lead(II) bromide), EAPbI 3(ethylammonium lead (II) iodide), or a combination thereof. For example, the second inorganic material may include gallium oxide, such as γ-gallium oxide, i.e., γ-Ga 2 O 3 For example, the second inorganic material may be γ-Ga 2 O 3 nanoparticles, and the γ-Ga 2 O 3 The nanoparticles may have a cubic crystal structure.
[0102] The thickness of the electron control layer 15 may be thinner than that of the electron transport layer 14, and may be, for example, about 0.2 to about 0.8 times, or about 0.3 to about 0.7 times the thickness of the electron transport layer 14. For example, the thickness of the electron control layer 15 may be in the range of about 1 nm to about 10 nm.
[0103] Optionally, another layer such as an electron injection layer (EIL) may be further included between the cathode 16 and the quantum dot layer 13. The electron injection layer (EIL) may facilitate electron injection from the cathode 16.
[0104] For example, the method of manufacturing the quantum dot device 10 may include: forming an anode 11 on a substrate, forming a hole transport layer 12 on the anode 11, forming a quantum dot layer 13 on the hole transport layer 12, forming an electron transport layer 14 and an electron control layer 15 on the quantum dot layer 13, and forming a cathode 16 on the electron transport layer 14 and the electron control layer 15, wherein the formation of the electron control layer 15 may be performed before the formation of the electron transport layer 14, after the formation of the electron transport layer 14, or a combination thereof. Here, the hole transport layer 12, the quantum dot layer 13, the electron transport layer 14, and the electron control layer 15 may be formed, for example, by a solution process such as spin coating, slit coating, inkjet printing, nozzle printing, spraying, blade coating, or a combination thereof, respectively, but are not limited thereto.
[0105] For example, the formation of the electron transport layer 14 may include: preparing a Zn precursor and an optional M precursor (wherein M is Mg, Co, Ni, Zr, Mn, Sn, Y, Al, or a combination thereof) by a sol-gel reaction. 1-x M x A dispersion for an inorganic electron transport layer of inorganic nanoparticles represented by O (0≤x<0.5), and coating the dispersion for an inorganic electron transport layer. Here, the solution may include, for example, an alcohol solvent such as methanol, ethanol, isopropanol, butanol, or a mixed solvent thereof.
[0106] For example, the formation of the electron control layer 15 may include: heat treating a solution including a Ga precursor to prepare a solution including γ-Ga 2 O 3A dispersion for an inorganic electronic control layer of inorganic nanoparticles represented by, and coating the dispersion for an inorganic electronic control layer. Here, the solution may include, for example, an amine solvent, for example, an alkylamine solvent, for example, oleylamine, but is not limited thereto. The heat treatment may be performed, for example, at about 70° C. to about 500° C., for example, at about 80° C. to about 450° C., for example, at about 100° C. to about 400° C.
[0107] The quantum dot device can be applied to various electronic devices, such as display devices or lighting devices.
[0108] Hereinafter, the embodiments are described in more detail with reference to examples. However, these examples are exemplary, and the present disclosure is not limited thereto.
[0109] Synthesis Example: Synthesis of Quantum Dots
[0110] (1) Synthesis of ZnTeSe core
[0111] Selenium (Se) and tellurium (Te) were dispersed in trioctylphosphine (TOP) to obtain a 2 molar (M) Se / TOP stock solution and a 0.1 M Te / TOP stock solution, respectively.
[0112] 0.125 mmol zinc acetate, 0.25 mmol oleic acid, and 0.25 mmol hexadecylamine were placed in a reactor together with 10 mL trioctylamine, and then heated under vacuum at 120° C. After 1 hour, the atmosphere in the reactor was replaced with nitrogen.
[0113] After the reactor was heated at 240° C., Se / TOP stock solution and Te / TOP stock solution were quickly added thereto at a Te / Se molar ratio of 1:25. After the temperature was raised to 300° C. and then the reaction solution was maintained for 30 minutes, the reaction solution was quickly cooled to room temperature, acetone was added thereto, and the precipitate obtained by centrifuging the mixture was dispersed in toluene to obtain a toluene dispersion of ZnTeSe core quantum dots.
[0114] (2) Synthesis of ZnTeSe core / ZnSeS shell quantum dots
[0115] Trioctylamine was placed in a 10 mL flask. 0.6 mmol of zinc acetate and 1.2 mmol of oleic acid were added thereto, and then treated at 120° C. under vacuum for 10 minutes. Subsequently, the mixture was stirred under nitrogen (N 2) After replacing the internal atmosphere of the flask, the toluene dispersion of the ZnTeSe core obtained in step (1) was quickly injected therein, then heated to 340°C, and reacted while adding a Se / TOP stock solution and a 1 molar concentration (M) S / TOP stock solution prepared by dispersing sulfur in trioctylphosphine at a Se / S molar ratio of 1.2:2.8. When the reaction was completed, the reactor was cooled, and the prepared nanocrystals were centrifuged with ethanol and dispersed in toluene to obtain a toluene dispersion of ZnTeSe / ZnSeS core / shell quantum dots.
[0116] Preparation Example 1: Preparation of a dispersion for an electron transport layer
[0117] 8.07 mmol of zinc acetate dihydrate, 0.93 mmol of magnesium acetate tetrahydrate and 90 mL of dimethyl sulfoxide were placed in a reactor and heated at 60° C. under air. Subsequently, 15 mmol of tetramethylammonium hydroxide pentahydrate was dissolved in 30 mL of ethanol, and the solution was added to the reactor in a dropwise manner at a rate of 3 mL / min. After the mixture was stirred for 1 hour, the prepared Zn 0.85 Mg 0.15 O nanoparticles and ethyl acetate were centrifuged at a volume ratio of 1:9 and dispersed in ethanol to obtain a dispersion of the nanoparticles with (by FEI Titan operating at 200 kV) TM G2 80-200TEM measurement) Zn with an average particle diameter of about 3.5nm 0.85 Mg 0.15 O nanoparticles solution.
[0118] Preparation Example 2: Preparation of a dispersion for an electronic control layer
[0119] 0.5 g of gallium acetylacetonate (Ga(acac) 3 ) and 7g of oleylamine as a solvent were put into a 100ml flask, and the mixture was heated up to 80°C. When gallium acetylacetonate was completely dissolved, the solution was degassed and heated up to 310°C at an average rate of 3°C / min while continuously stirring under an argon atmosphere. Subsequently, after the temperature was lowered to 150°C, tri-n-octylphosphine oxide (TOPO) was injected therein, and the obtained mixture was stirred for 30 minutes. When the reaction was completed, the reactor was cooled, and the prepared nanocrystals were centrifuged with ethanol and then dispersed in hexane or toluene to obtain nanocrystals having (by FEI Titan operated at 200kV) dispersed therein. TM γ-Ga with a particle size distribution of about 4 nanometers (nm) to 7 nm (measured by G2 80-200TEM) 2 O 3 Dispersion of Nanoparticles.
[0120] Evaluation I
[0121] The dispersion for an electron control layer according to Preparation Example 2 was spin-coated to a thickness of 10 nm, and heat-treated at 80° C. for 30 minutes to form a thin film.
[0122] Figure 4 is a diagram showing an X-ray diffraction (XRD) pattern of a thin film obtained from the dispersion for an electron control layer obtained in Preparation Example 2, Figure 5 and Figure 6 are graphs showing the results of X-ray photoelectron spectroscopy (XPS) analysis of a thin film obtained from the dispersion for an electron control layer obtained in Preparation Example 2, and Figure 7 is an atomic force microscope (AFM) photograph showing the morphology of a thin film obtained from the dispersion for an electron control layer obtained in Preparation Example 2.
[0123] Reference Figures 4 to 7 , the thin film obtained from the dispersion for the electron control layer obtained in Preparation Example 2 shows that γ-Ga having a cubic crystal structure 2 O 3 The nanoparticles are relatively evenly distributed. 2 O 3 The nanoparticles had a particle size distribution ranging from about 4 nm to 7 nm, an exciton peak of 302 nm, an energy band gap of 3.08 electron volts (eV), a peak emission wavelength of 425 nm, and an average roughness (Rq) of 2.52 nm.
[0124] Fabrication of quantum dot devices
[0125] Example 1
[0126] A glass substrate deposited with ITO (work function (WF): 4.8 eV) as an anode was surface treated with ultraviolet (UV)-ozone for 15 min, spin-coated with a poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) solution (HC Starks Co., Ltd.), and heat-treated at 150°C for 10 min in an air atmosphere, and then heated under N 2The film was heat treated at 150°C for 10 minutes under an atmosphere to form a 30 nm thick hole injection layer (highest occupied molecular orbital (HOMO) energy level: 5.3 eV and lowest unoccupied molecular orbital (LUMO) energy level: 2.7 eV). Subsequently, a 25 nm thick hole transport layer (HOMO energy level: 5.6 eV and LUMO energy level: 2.69 eV) was formed on the hole injection layer by spin coating a poly[(9,9-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-butylphenyl))-diphenylamine)] (TFB) solution (Sumitomo) and heat treating it at 150°C for 30 minutes. On the hole transport layer, a 20 nm thick quantum dot layer (HOMO energy level: 5.7 eV and LUMO energy level: 2.97 eV) was formed by spin coating the ZnTeSe / ZnSeS core-shell quantum dots obtained in the synthesis example, and heat treating it at 80°C for 30 minutes. On the quantum dot layer, a 10 nm thick electron control layer was formed by spin coating the dispersion for the electron control layer obtained in Preparation Example 2, and heat treating it at 80°C for 30 minutes. On the electron control layer, a 20 nm thick electron transport layer (HOMO energy level: 8.0 eV and LUMO energy level: 4.3 eV) was formed by spin coating the dispersion for the electron transport layer obtained in Preparation Example 1, and heat treating it at 80°C for 30 minutes. On the electron transport layer, a cathode was formed by depositing aluminum (Al) to a thickness of 100 nm under vacuum to manufacture a quantum dot device.
[0127] Comparative Example 1
[0128] A quantum dot device was prepared according to the same method as Example 1, except that no electron control layer was formed.
[0129] Evaluation II
[0130] The current-voltage-luminescence characteristics of the quantum dot devices according to Example 1 and Comparative Example 1 were evaluated.
[0131] The current-voltage-luminescence characteristics were evaluated by using a Keithley 220 source meter and a Minolta CS200 spectroradiometer.
[0132] The results are shown in Table 1.
[0133] Table 1
[0134]
[0135] *EQE max : Maximum external quantum efficiency
[0136] *EQE@500nit: External quantum efficiency at 500 nits (cd / m2)
[0137] *Brightness (Cd / m 2 )@5mA: Brightness at 5mA
[0138] *T60@325nit: The time it takes for the brightness to decrease to 60% at a constant current of the initial 325 nit reference
[0139] *λ max : Peak emission wavelength
[0140] Referring to Table 1, compared with the quantum dot device according to Comparative Example 1, the quantum dot device according to Example 1 showed improved efficiency and lifetime.
[0141] While the present disclosure has been described in connection with what are presently considered to be practical example embodiments, it is to be understood that the invention is not limited to the disclosed embodiments, but on the contrary is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
Claims
1. Quantum dot devices, including: The anode and cathode face each other, a quantum dot layer between the anode and the cathode, a hole transport layer between the anode and the quantum dot layer, the hole transport layer being configured to enhance hole transport properties from the anode to the quantum dot layer, an inorganic electron transport layer between the cathode and the quantum dot layer, the inorganic electron transport layer being configured to enhance electron transport properties from the cathode to the quantum dot layer, and an inorganic electron control layer between the cathode and the quantum dot layer, the inorganic electron control layer being configured to reduce electron transport properties from the cathode to the quantum dot layer, wherein the inorganic electron transport layer comprises a first inorganic material, and the inorganic electron control layer comprises a second inorganic material different from the first inorganic material, wherein the second inorganic material comprises γ-Ga2O3 nanoparticles having an average particle size less than or equal to 10 nanometers, and The thickness of the inorganic electron control layer is 0.2 to 0.8 times the thickness of the inorganic electron transport layer.
2. The quantum dot device of claim 1, wherein the inorganic electron control layer is disposed between the cathode and the inorganic electron transport layer, between the quantum dot layer and the inorganic electron transport layer, or a combination thereof.
3. The quantum dot device of claim 1, wherein the first inorganic material comprises an oxide containing zinc.
4. The quantum dot device of claim 3, wherein the oxide containing zinc is Zn 1-x M x O represents, wherein M is Mg, Co, Ni, Zr, Mn, Sn, Y, Al, or a combination thereof, and 0≤x<0.
5. 5 . The quantum dot device of claim 1 , wherein the first inorganic material comprises nanoparticles having an average particle size less than or equal to 10 nanometers.
6. The quantum dot device of claim 1, wherein the lowest unoccupied molecular orbital energy level of the inorganic electronic control layer is lower than The lowest unoccupied molecular orbital energy level of the quantum dot layer and The lowest unoccupied molecular orbital energy level of the inorganic electron transport layer.
7. The quantum dot device of claim 1, wherein the energy band gap of the inorganic electronic control layer is greater than The energy band gap of the quantum dot layer and The inorganic electron transport layer has an energy band gap. 8 . The quantum dot device of claim 1 , wherein the thickness of the inorganic electron control layer is 0.3 to 0.7 times the thickness of the inorganic electron transport layer.
9. The quantum dot device of claim 1, wherein the thickness of the inorganic electronic control layer is 1 nanometer to 10 nanometers.
10. The quantum dot device of claim 1, wherein the quantum dot layer comprises non-cadmium based quantum dots.
11. The quantum dot device of claim 10, wherein The non-cadmium-based quantum dots include: Zinc and Tellurium, selenium, or a combination thereof, or Indium and Zinc, phosphorus, or a combination thereof.
12. The quantum dot device of claim 11, wherein the quantum dot comprises: Contains the following cores: Zinc and Tellurium, selenium, or a combination thereof, or Indium and phosphorus, and optionally zinc, and A shell is disposed on at least a portion of the core, the shell comprising a different composition than the core.
13. The quantum dot device of claim 12, wherein the shell comprises ZnSeS, ZnS, or a combination thereof.
14. A method for manufacturing a quantum dot device as claimed in any one of claims 1 to 13, comprising: Forming an anode, forming a hole transport layer on the anode, forming a quantum dot layer on the hole transport layer, forming an inorganic electron transport layer on the quantum dot layer, forming an inorganic electronic control layer on the quantum dot layer, and forming a cathode on the inorganic electron transport layer and the inorganic electron control layer, wherein the formation of the inorganic electron control layer is performed before the formation of the inorganic electron transport layer, after the formation of the inorganic electron transport layer, or a combination thereof, The formation of the quantum dot layer, the formation of the inorganic electron transport layer, and the formation of the inorganic electron control layer are each performed using a solution process, and The formation of the inorganic electronic control layer comprises heat treating a solution including a Ga precursor to prepare a dispersion for an inorganic electronic control layer including inorganic nanoparticles represented by γ-Ga2O3, and The dispersion for an inorganic electronic control layer is applied.
15. The method of claim 14, wherein The formation of the inorganic electron transport layer comprises: A solution comprising a Zn precursor and an optional M precursor is used to prepare a Zn precursor wherein 0≤x<0.5 by a sol-gel reaction. 1-x M x A dispersion of inorganic nanoparticles for an inorganic electron transport layer represented by O, wherein M is Mg, Co, Ni, Zr, Mn, Sn, Y, Al, or a combination thereof, and The dispersion for an inorganic electron transport layer is applied.
16. An electronic device comprising the quantum dot device according to any one of claims 1 to 13.
Citation Information
Patent Citations
Method for SiC Coating of Graphite Base Substrate
KR1020190005324A
Quantum dot light-emitting device and display device and lighting device with same
CN106654026A
Quantum dot light emitting diode and preparation method thereof
CN107910449A
Quantum dot electroluminescent device and preparation method thereof
CN109148704A